Translation of the talk test to exercise prescription - Jeanes, Elizabeth (My University, 2010)
In exercise prescription, intensity is the most difficult variable to define. Intensity is defined by %HRmax or % of maximal METS. An alternative method of measuring exercise intensity is the TT (Talk Test). The purpose of the current study was to determine how much of a reduction in absolute intensity from an incremental exercise test was needed to allow for comfortable speech during exercise training. Fourteen physically active subjects participated in the study. Subjects performed multiple incremental exercise tests and three 40-minute training bouts based on one stage before the Last Positive (LP-1), Last Positive (LP) or equivocal (EQ) TT. All training bouts resulted in %HRmax values within the recommend range of 64-94%. Training bouts based on the LP- 1 and LP produced RPE values within the recommended guidelines of moderate to hard (3-5). The majority of subjects could speak comfortably when they trained at the exercise bout based on the LP-1 or LP TT. There was no significant difference between speed, heart rate or RPE at any matched stage of repeated incremental tests. This study concluded that in order for an individual to speak comfortable, the individual must work at an intensity no higher than their LP TT.
Keywords: Exercise tests; Exercise -- Physiological aspects